Prediksi Debit Banjir Rancangan Menggunakan Metode Hidrograf Satuan SCS pada DAS Aesesa untuk Mitigasi Resiko Banjir - Ralno Robson Klau; Denik Sri Krisnayanti; Jakobis Johanis Messakh (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2026)
The Aesesa River Basin is located in the Ngada and Nagekeo Regencies on Flores Island, with a basin area of 1,169.24 km2. The purpose of this research is to analyze the flood discharge of the Aesesa River Basin based on the Natural Resources Conservation Service (NRCS), USA Curve Number infiltration method, and the Synthetic Unit Hydrograph (SCS) method. Rainfall data used satellite TRMM corrected with rain gauge data, with a data length of 20 years (2000 – 2019). Observed discharge using the Boasaby staff gauge (SG) and basin characteristics using the Geographical Information System (GIS). Design rainfall analysis used the Generalized Extreme Value (GEV) distribution. Flood analysis used the soil conservation service synthetic unit hydrograph method (HSS SCS) with the aid of HEC-HMS software. The research results show that land cover is dominated by savanna and shrub vegetation, and soil types with low permeability result in a CN value of 77.77. Flood discharge analysis was subsequently performed for various return periods. The observed flood discharge obtained from hydraulic calculations using the continuity equation was approximately 405.19 m³/s. The calculated flood discharge for the 2-year return period was 250.10 m3/s. Meanwhile, at return periods of 5, 10, 25, 50, 100, 200, 500, and 1000 years, the flood discharge is 480.10 m3/s, 691.80 m3/s, 1036.10 m3/s, 1365.90 m3/s, 1759.70 m3/s, 2231.00 m3/s, 3020.90 m3/s, and 3755.30 m3/s respectively, all exceeding the observed flood discharge. These results indicate that the relatively high Curve Number (CN) value in the Aesesa Watershed reflects low infiltration capacity, thereby contributing to increased surface runoff.